Development of PhET Simulation-Based Worksheet on Newton's Law Materials at SMA Negeri 1 Gorontalo - Hajrah Safitri; Raghel Yunginger; Dewa Eka Setiawan; Abdul Wahidin Nuayi; Asri Arbie; Abdul Haris Odja; Nova Elysia Ntobuo (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
This research aims to develop a PhET simulation-based worksheet in physics learning on Newton's Law material in Class X SMA Negeri 1 Gorontalo. This research design uses a 4-D design which is limited to the Development stage. The subjects of this study were students of class X IPA 2 SMA Negeri 1 Gorontalo in the 2021/2022 academic year. The development of PhET simulation-based worksheets is seen in 3 indicators, namely validity, practicality, and effectiveness. Based on the results of the validity shows that the standard of the feasibility of content, language, appearance, construction, and readability with a percentage of 67% is included in the valid category. This shows that the PhET simulation-based worksheets meet the validity criteria. While practicality is seen from the implementation of activities in worksheets by teachers, it shows that all aspects of activities are carried out with an average percentage for all meetings of 96%, while at the first meeting one aspect is not implemented, namely the teacher does not explain the display on the PhET simulation. This shows that the PhET simulation-based worksheets meet the criteria for practicality. For effectiveness, it is seen from the aspect of student activities and student learning outcomes. The percentage of student activity for all meetings is 89%, and student activity aspects of accessing PhET simulation links and conducting experiments on PhET simulations are relatively easy aspects for students to do. The results of the analysis of student test data after using the PhET simulation-based worksheets showed that the cognitive domain of C3 had a greater difference between pretest and posttest of 52% with an increase in N-gain value of 0.8% including high criteria compared to C2 and C4. This shows that the PhET simulation-based worksheets meet the effectiveness criteria.